Achy But Healthy : Lessons From the Israeli Health Sector - Kop, Yaakov (IMF Working Papers; Working Paper, 1994)
Health policy has been for some time high on the agenda of many countries--and where it has not, it should be. Since no ideal model of health services has ever been devised 9 one may look for favorable elements in the health sector of a given country and examine their applicability to other countries. This paper analyzes Israel's health sector in this context.